The Effect Of Yoga On Pressure Blood In Hypertension Patients - Sani, Fakhrudin Nasrul; Widiastuti, Agung; Irawan, Ady; Rista, Rista (LPPM Universitas Duta Bangsa Surakarta, 2025)
Hypertension is a chronic disease with a high prevalence in Southeast Asia and Indonesia. Yoga as a non- pharmacological therapy has the potential to effectively lower blood pressure. This study used a quantitative method with a quasi-experimental one-group pretest-posttest design, involving 30 hypertension patients participating in a chronic disease service program at the Grogol Community Health Center. Yoga exercises were carried out for three consecutive days with a duration of 30-60 minutes per session. Data were collected using a general data sheet and a blood pressure monitor. The results of the Wilcoxon test showed a significant decrease in systolic and diastolic blood pressure after the yoga intervention (p = 0.000). Yoga exercises play a role in improving heart function, reducing sympathetic nerve activity, and causing vasodilation, resulting in lower blood pressure. This study concluded that yoga exercises are effective as a non-pharmacological intervention that can improve the quality of life of hypertension patients and is recommended for routine implementation in the community.